SURDEZ E FAMÍLIA: INTERAÇÃO FAMILIAR NO COTIDIANO COMUNICATIVO DO ALUNO SURDO - Freire, Freire; Nascimento, Adriana Paula Oliveira; Raimundi, Ana Paula; Tavares, Ellen Paula do Nascimento; Alves, Priscila Biaggi (Seminário Transdisciplinar da Saúde, 2018)
>>> ver pdf